Psychological Biases and Investment Decisions: A Study of Economic Students: Bias Psikologis dan Keputusan Investasi: Studi Mahasiswa Ekonomi - Hussalman, Akhmad Irsyadin Alain Naufal; Sari, Helinda Maya Kumala (Indonesian Journal of Law and Economics Review, 2023)
This research employs a quantitative approach to investigate the impact of financial literacy, regret aversion, herding bias, and the illusion of control on investment decisions among students in the Faculty of Economics and Business at Muhammadiyah University of Sidoarjo. Utilizing a purposive sampling technique, data were collected from 210 students through a validated and reliable questionnaire distributed via Google Forms. The results reveal that while financial literacy exhibits a non-significant influence on investment decisions, regret aversion and the illusion of control significantly affect these decisions. In contrast, herding bias demonstrates an influence that is not statistically significant. This study underscores the importance of psychological factors in shaping investment choices among aspiring economic professionals, with implications for financial education and decision-making strategies in the field. Highlights: Financial Literacy's Limited Influence: This research highlights that despite its importance, financial literacy does not significantly impact investment decisions among students in the Faculty of Economics and Business. Psychological Biases Matter: The study underscores the significance of psychological factors such as regret aversion and the illusion of control in shaping investment decisions, emphasizing the need to address these biases in financial education. Herding Bias Ineffectiveness: While herding bias plays a role, this study finds that its influence on investment decisions is not statistically significant, indicating room for further investigation into its practical implications. Keywords: Financial Literacy, Investment Decisions, Regret Aversion, Herding Bias, Illusion of Control